P154 Diffuse skewing of Th17/Treg ratio in the anorectal mucosa of HIV+MSM with HPV-associated dysplasia. (14th July 2019) - Choi, Yoojin; Salit, Irving; Grech, Sarah; Sano, Marie; Weiss, Edward; Kovacs, Colin; Paquette, Rachelle; Claudio, Marian; Severini, Alberto; Kaul, Rupert
Abstract : Background: Anal Human Papillomavirus (HPV) infection is common in MSM. While most HPV infections resolve spontaneously, some persist and cause anal intraepithelial neoplasia (AIN) that can progress to anal cancer. To better understand the mucosal immunopathogenesis of HPV/AIN, we compared mucosal T cell subsets between AIN-free mucosa and AIN lesions within HIV+ART+ MSM. Methods: Anal swabs from 46 participants were used to 1) screen for 46 mucosal HPV types by microsphere-based genotyping and 2) test for HIV RNA levels by RT-PCR. AIN-free mucosa was biopsied, and (where applicable) additional biopsies were taken from histology-confirmed areas of AIN. Treg markers (CD25, FoxP3) and a Th17 marker (CCR6) were assessed by flow cytometry. Statistical comparisons were assessed between groups (Mann-Whitney) and within the same individual (Wilcoxon). Results: Th subsets were first compared between clinically normal mucosa and AIN lesions within AIN+ individuals, and no lesion-specific alterations were apparent. When we compared clinically normal mucosa between study groups, participants with high-grade AIN had a reduced Th17/Treg ratio compared to participants with no AIN (HGAIN= 7.83, No AIN= 19.75; p= 0.007) or participants with low-grade AIN (LGAIN= 14.1; p= 0.017). This difference was primarily driven by an increase in Treg frequencies (HGAIN= 4.00%, LGAIN= 2.38%, No AIN= 1.88%; p= 0.048), and participants with HPV16/18 also had significantly higher Treg frequencies (HPV16/18= 4.02%, No HPV16/18= 2.68%; p= 0.021). Th17 frequencies did not vary with HPV status, HPV16/18 positivity or AIN stage. No mucosal parameters were associated with anorectal HIV RNA detection. Conclusion: HPV infection and high-grade AIN were associated with diffuse mucosal Treg infiltration, reducing the mucosal Th17/Treg ratio in participants with high-grade AIN. While changes in T cell immunology did not increase HIV RNA shedding in ART+ MSM, their effect on ART-naïve men or HIV susceptibility in HIV-negative men will be interesting areas for future research. Disclosure: No significant relationships.